Integrated high-performance lining brick for converter and preparation method thereof
By using integrated high-performance lining bricks in the converter and connecting magnesium carbon bricks and magnesium bricks with slot structures, the problems of cumbersome and long time in traditional masonry are solved, and the effect of simplifying the process and shortening the time is achieved.
Patent Information
- Application Number
- CN202310259056.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-17
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-03-17
AI Technical Summary
During the masonry of traditional converter, the working layer of magnesium carbon bricks and permanent layer of magnesium bricks need to be built separately, which increases the masonry process, reduces the masonry progress, increases the construction difficulty, and increases the masonry time, which cannot meet the steel plant. Strict requirements for masonry time.
The integrated high-performance lining brick is adopted to connect the permanent layer of magnesium bricks and the working layer of magnesium carbon bricks through the slot structure, simplifying the masonry process and shortening the masonry time.
The masonry process is simplified, the masonry time is greatly shortened, the steel plant's requirements for masonry time are met, and the integrity of the converter lining resistance material is improved.
Smart Images

Figure CN116411149B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of refractory materials for steel smelting converters, and relates to an integrated high-performance lining brick for a converter and a preparation method thereof, and specifically relates to an integrated high-performance lining brick for a converter with a working layer of magnesia carbon bricks and a permanent layer of magnesia bricks, and a preparation method thereof. Background Art
[0002] The converter is a type of steelmaking furnace, generally referring to a cylindrical oxygen-blowing steelmaking container that can be tilted. Converter steelmaking uses molten iron, scrap steel, and ferroalloys as the main raw materials. It does not rely on external energy sources, but relies on the physical heat of the molten iron itself and the chemical reaction between the components of the molten iron to generate heat, and completes the steelmaking process in the converter. Converters are divided into acidic and alkaline converters according to the properties of refractory materials; they are divided into top-blown, bottom-blown, side-blown, and top-bottom combined-blown converters according to the location where the gas is blown into the furnace; and they are divided into air and oxygen converters according to the type of gas blown in. Converter steelmaking mainly plays the role of decarbonization, dephosphorization, desulfurization, deoxidation, removal of harmful gases and impurities, adjustment of temperature, and adjustment of composition.
[0003] The refractory material of the converter metal shell lining is generally divided into three parts: the thermal insulation layer, the permanent layer, and the working layer. The thermal insulation layer plays the role of heat insulation and heat preservation, and generally uses refractory fiberboard as the thermal insulation material; the permanent layer plays the role of heat insulation, heat preservation, and improving the safety factor, and generally uses fired magnesia bricks as the refractory material of the permanent layer; the working layer is directly exposed to the erosion of molten steel, slag, furnace gas, etc., and generally uses magnesia carbon bricks as the refractory material of the working layer.
[0004] Magnesia carbon bricks are unburned refractory materials made of high-melting-point magnesia sand and high-melting-point carbon materials that are difficult to be wetted by slag as raw materials, various non-oxide additives are added, and they are combined with carbon binders. Magnesia carbon bricks are mainly used for the lining of converters, AC arc furnaces, DC arc furnaces, slag lines of ladles, etc. They have good thermal shock stability, high temperature resistance, strong resistance to slag erosion, good thermal shock resistance, and low high-temperature creep.
[0005] Burnt magnesia bricks refer to alkaline refractory products that are burned with magnesia as the main raw material. Burnt magnesia bricks are mainly used for the furnace walls and bottoms of alkaline steelmaking open-hearth furnaces and electric furnaces, permanent linings of oxygen converters, iron-mixing furnaces, nonferrous smelting furnaces, and high-temperature tunnel kilns; the linings of rotary kilns for calcining magnesia and cement, the upper checker bricks of glass melting furnaces, and the bottoms and ends of steel rolling soaking furnaces and heating furnaces. Burnt magnesia bricks have a high refractoriness under load and strong resistance to alkaline slag erosion, but poor thermal shock resistance and very weak resistance to acidic slag erosion. They also require high-temperature burning, which pollutes the environment, has complicated processes, and high manufacturing costs.
[0006] As an important part of the steelmaking system, the converter is of great significance to blast furnace ironmaking, production scheduling, and steel production. Therefore, it is particularly important to control the laying time of the converter lining refractory materials, and the steel mill also has strict regulations on the laying time of the lining refractory materials. In the traditional converter laying process, the working layer magnesia carbon bricks and the permanent layer magnesia bricks need to be laid separately, which increases the laying process, reduces the laying progress, increases the construction difficulty, and also increases the laying time. With the steel mill's converter steelmaking, the amount of scrap iron added has increased, and the quality requirements for steel have become higher and higher, resulting in an increasingly harsh use environment for converter magnesia carbon bricks, and higher and higher requirements for the slag erosion resistance of converter magnesia carbon bricks.
[0007] Therefore, how to develop a high-performance lining brick for a converter with a simple production process and simple construction, which is an integrated working layer of magnesia carbon bricks and a permanent layer of magnesia bricks, is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention
[0008] In view of this, the present invention provides an integrated high-performance lining brick for a converter comprising a working layer of magnesia carbon bricks and a permanent layer of magnesia bricks.
[0009] In order to achieve the above object, the present invention adopts the following technical solution:
[0010] An integrated high-performance lining brick for a converter comprises a brick body, wherein the brick body comprises a permanent layer of magnesia bricks and a working layer of magnesia-carbon bricks, and the permanent layer of magnesia bricks and the working layer of magnesia-carbon bricks are connected via a slot structure.
[0011] Beneficial effects of the invention: The integrated high-performance lining bricks of the invention solve the problems of separate construction of the working layer magnesia carbon bricks and the permanent layer magnesia bricks, cumbersome construction, and long construction time during converter construction. The construction process can be simplified, the construction time can be greatly shortened, the construction task can be completed within the specified time, the requirements of the steel plant can be met, and the integrity of the converter lining refractory can be improved.
[0012] Furthermore, a plurality of card blocks are provided on one side of the permanent layer magnesia bricks, and a plurality of card slots are provided on one side of the working layer magnesia carbon bricks, and the card blocks are adapted to the card slots.
[0013] Furthermore, the above-mentioned card block is a T-shaped card block or an L-shaped card block.
[0014] Furthermore, the longitudinal section of the brick body is a quasi-isosceles trapezoid, and the lower bottom of the quasi-isosceles trapezoid, i.e. the other side of the permanent layer of magnesium bricks, is designed with an arc, which is the same as the arc of the converter shell used.
[0015] The beneficial effect of adopting the above further technical solution: the tail of the integrated high-performance lining brick of the present invention adopts a curved design, which can fit more closely with the refractory fiberboard of the insulation layer during masonry, reduce masonry gaps, and improve masonry quality and safety factor.
[0016] Further, the working layer magnesia carbon brick is made of the following raw materials in parts by weight: 10-30 parts of 3.5mm-6mm magnesia aggregate, 10-30 parts of 1-3.5mm magnesia aggregate, 10-30 parts of 0-1mm magnesia aggregate, 3-20 parts of F100-F200 magnesia powder, 10-18 parts of F100 flake graphite, 0.2-2 parts of solid resin powder, 0.5-3 parts of F325 chromium oxide green, 0.5-3 parts of 5μm-15μm microcrystalline corundum powder, 0.5-4.5 parts of F200 magnesium aluminum alloy powder, and 2.5-3.5 parts of liquid phenolic resin;
[0017] The permanent layer magnesia brick is made of the following raw materials in parts by weight: 10-30 parts of 3.5mm-6mm magnesia aggregate, 10-30 parts of 1-3.5mm magnesia aggregate, 10-30 parts of 0-1mm magnesia aggregate, 0-20 parts of 3.5mm-6mm waste magnesium spinel brick, 0-20 parts of 1-3.5mm waste magnesium spinel brick, 0-20 parts of 0-1mm waste magnesium spinel brick, 3-20 parts of F100-F200 magnesia powder, 0.05-0.2 parts of 2mm explosion-proof fiber, 0.2-2 parts of solid resin powder, 0.5-3 parts of 5μm-15μm microcrystalline corundum powder, 0.5-4.5 parts of F200 magnesium-aluminum alloy powder, 2-10 parts of 5-15μm magnesium-aluminum spinel powder, 2.5-3.5 parts of liquid phenolic resin, and 0.1-0.3 parts of methenamine.
[0018] The beneficial effects of adopting the above further technical solutions: the chromium oxide green and microcrystalline corundum powder are introduced into the integrated high-performance lining brick working layer magnesia carbon brick of the present invention, which can improve the slag erosion resistance and scouring resistance of the brick blank, and play an important role in resisting the scouring erosion of molten steel and high-temperature flue gas. The microcrystalline corundum powder is introduced into the permanent layer magnesia brick, which also has the advantages of improving the density and strength of the brick blank, improving the erosion resistance, etc.; in addition, the explosion-proof fiber is introduced, which can improve the thermal shock stability of the brick blank, reduce the thermal conductivity, and improve the thermal insulation effect.
[0019] Furthermore, the solid resin powder is a thermosetting solid phenolic resin, and the explosion-proof fiber is a polypropylene fiber.
[0020] The present invention also provides a method for preparing the above-mentioned integrated high-performance lining brick for a converter, comprising the following steps:
[0021] (1) Weighing various raw materials according to the above-mentioned integrated high-performance lining brick for converter;
[0022] (2) Mixing and secondary molding operations:
[0023] (a) mixing the raw material of permanent layer magnesia brick with a wet mill to obtain permanent layer magnesia brick mud; mixing the raw material of working layer magnesia carbon brick with a high-speed mixer to obtain working layer magnesia carbon brick mud;
[0024] (b) placing the permanent layer magnesia brick mud into a permanent layer magnesia brick mold and pressing it into shape to obtain a preliminarily formed magnesia brick blank;
[0025] (c) placing the initially formed magnesia brick blank into the corresponding position in the mold cavity of the integrated lining brick mold, and then loading the working layer magnesia carbon brick mud into the mold cavity of the integrated lining brick mold, and performing a second pressing molding to obtain an integrated lining brick blank of the working layer magnesia carbon brick and the permanent layer magnesia brick;
[0026] (3) Drying the integrated lining brick blanks of the working layer magnesia carbon bricks and the permanent layer magnesia bricks to obtain the integrated high-performance lining bricks for the converter.
[0027] Beneficial effects of the present invention: the one-piece high-performance lining bricks prepared by the present invention have the functions of heat insulation, thermal insulation, and improved safety factor. In addition, the integrity of the refractory material of the converter lining can be improved. The working layer magnesia carbon bricks have good thermal shock stability, high temperature resistance, strong resistance to slag erosion, low high-temperature creep and other excellent characteristics; the permanent layer magnesia bricks have good high temperature resistance, high load softening temperature, good thermal shock stability, high room temperature compressive strength, strong resistance to alkaline slag erosion and other advantages. Compared with fired magnesia bricks, the one-piece high-performance lining brick permanent layer magnesia bricks of the present invention have a simple production process and no high-temperature firing process, and are free from dependence on high-temperature tunnel kilns, etc., reduce manufacturing costs, save resources, respond to the national call for energy conservation and emission reduction, and are beneficial to environmental protection.
[0028] Furthermore, in step (a), the permanent layer magnesia brick raw material is mixed with a wet mill, the mixing speed is 60-120 rpm, the net mixing time is 20-40 min, and the discharge temperature is 45-55° C.;
[0029] The raw materials of the working layer magnesia carbon bricks are mixed with a high-speed mixer, the mixing speed is 120-360 rpm, the net mixing time is 10-30 min, and the discharge temperature is 50-60°C.
[0030] Further, in step (b), the above compression molding, the molding pressure is 6300-1500KN, and the compression is performed 2-3 times to obtain a strength of 20-40Mpa and a density of 2.5-2.8g / cm 3 The initial formed magnesia brick green.
[0031] Furthermore, in step (c), the second pressing and molding is performed at a molding pressure of 10000-20000 KN and the pressing is performed 8-12 times to obtain an integrated lining brick blank of a working layer of magnesia carbon bricks and a permanent layer of magnesia bricks.
[0032] The beneficial effects of adopting the above further technical solution are as follows: the overall strength of the brick blanks using the above molding process is high, the bonding strength between the magnesia bricks and the magnesia carbon bricks is high, and there is no problem of breakage between the two.
[0033] Furthermore, in step (3), the drying temperature is 200-300°C, the drying time is 12-20h, and the strength of the magnesia carbon brick part of the integrated high-performance lining brick for the converter is 25-40Mpa and the density is 2.96-3.06g / cm 3 The strength of the above-mentioned magnesia brick part is 80-120Mpa and the density is 3.00-3.13g / cm.
[0034] The beneficial effects of adopting the above-mentioned further technical scheme are as follows: the drying temperature is greater than the curing temperature of the phenolic resin, and the overall drying time is greater than 12 hours, which can fully ensure that the phenolic resin in the brick is completely cured, which is beneficial to improving the room-temperature compressive strength and overall performance of the brick, reducing the damage to the brick during the masonry process, and is beneficial to improving the overall masonry quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a schematic diagram of the structure of an integrated high-performance lining brick for a converter according to the present invention.
[0036] Figure 2 It is a schematic diagram of the structure of the permanent layer magnesia brick blank after the first preliminary forming of the present invention.
[0037] Figure 3 It is a schematic diagram of the structure of the working layer magnesia carbon brick after the second pressing and forming of the present invention.
[0038] Figure 4 This is a schematic diagram of the planed surface of the converter lining refractory body.
[0039] In the figure:
[0040] 1-brick body, 2-permanent layer of magnesia bricks, 3-working layer of magnesia-carbon bricks, 4-slot structure, 5-block, 6-slot, 7-isosceles trapezoidal lower bottom, 8-converter shell, 9-insulating layer of refractory fiberboard. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] The integrated high-performance lining brick for a converter comprises a brick body 1, wherein the brick body comprises a permanent layer of magnesia bricks 2 and a working layer of magnesia-carbon bricks 3, and the permanent layer of magnesia bricks 2 and the working layer of magnesia-carbon bricks 3 are connected via a slot structure 4.
[0043] In one embodiment, a plurality of blocks 5 are provided on one side of the permanent layer magnesia bricks 2 , and a plurality of slots 6 are provided on one side of the working layer magnesia carbon bricks 3 , and the blocks 5 are adapted to the slots 6 .
[0044] In one embodiment, the block 5 is a T-shaped block or an L-shaped block.
[0045] In one embodiment, the longitudinal section of the brick body 1 is an isosceles trapezoid, and the lower bottom 7 of the isosceles trapezoid, that is, the other side of the permanent layer of magnesium brick, adopts a curvature design, which is the same as the curvature of the converter shell 8 used. During masonry, it can fit more closely with the insulation layer refractory fiberboard 9, reducing masonry gaps and improving masonry quality and safety factor.
[0046] In one embodiment, the working layer magnesia carbon brick 3 is made of the following raw materials in parts by weight: 10-30 parts of 3.5mm-6mm magnesia aggregate, 10-30 parts of 1-3.5mm magnesia aggregate, 10-30 parts of 0-1mm magnesia aggregate, 3-20 parts of F100-F200 magnesia powder, 10-18 parts of F100 flake graphite, 0.2-2 parts of solid resin powder, 0.5-3 parts of F325 chromium oxide green, 0.5-3 parts of 5μm-15μm microcrystalline corundum powder, 0.5-4.5 parts of F200 magnesium aluminum alloy powder, and 2.5-3.5 parts of liquid phenolic resin;
[0047] The permanent layer magnesia brick 2 is made of the following raw materials in parts by weight: 10-30 parts of 3.5mm-6mm magnesia aggregate, 10-30 parts of 1-3.5mm magnesia aggregate, 10-30 parts of 0-1mm magnesia aggregate, 0-20 parts of 3.5mm-6mm waste magnesium spinel bricks, 0-20 parts of 1-3.5mm waste magnesium spinel bricks, 0-20 parts of 0-1mm waste magnesium spinel bricks, 3-20 parts of F100-F200 magnesia powder, 0.05-0.2 parts of 2mm explosion-proof fiber, 0.2-2 parts of solid resin powder, 0.5-3 parts of 5μm-15μm microcrystalline corundum powder, 0.5-4.5 parts of F200 magnesium-aluminum alloy powder, 2-10 parts of 5-15μm magnesium-aluminum spinel powder, 2.5-3.5 parts of liquid phenolic resin, and 0.1-0.3 parts of methenamine.
[0048] In one embodiment, the solid resin powder is a thermosetting solid phenolic resin, and the explosion-proof fiber is a polypropylene fiber.
[0049] Example 1
[0050] A method for preparing an integrated high-performance lining brick for a converter comprises the following steps:
[0051] (1) Weigh each raw material;
[0052] Table 1 Example 1 Working layer magnesia carbon brick raw material ratio table
[0053]
[0054] Table 2 Example 1 Permanent layer magnesia brick raw material ratio table
[0055]
[0056]
[0057] (2) Mixing and secondary molding operations:
[0058] (a) The permanent layer magnesia brick raw material is mixed with a wet mill to obtain a permanent layer magnesia brick mud material, the mixing speed is 100 rpm, the net mixing time is 30 min, and the discharge temperature is 52°C; the working layer magnesia carbon brick raw material is mixed with a high-speed mixer to obtain a working layer magnesia carbon brick mud material, the mixing speed is 360 rpm, the net mixing time is 15 min, and the discharge temperature is 55°C);
[0059] (b) The permanent layer magnesia brick mud is loaded into the permanent layer magnesia brick mold and pressed by an 800-ton electric screw brick press. The molding pressure is 8000KN. Pressing is performed 3 times to obtain a strength of 30±5Mpa and a density of 2.78±0.04g / cm 3 The initial forming of magnesia brick green;
[0060] (c) The initially formed magnesia brick blank is placed in the corresponding position in the cavity of the integrated lining brick mold, and then the working layer magnesia carbon brick mud is loaded into the cavity of the integrated lining brick mold. A 1600-ton electric screw brick press is used for the second pressing and molding. The molding pressure is 16000KN, and it is pressed 12 times to obtain an integrated lining brick blank of the working layer magnesia carbon brick and the permanent layer magnesia brick. The overall strength of the brick blank is high, and the bonding strength between the magnesia brick and the magnesia carbon brick is high, and there is no problem of breakage between the two.
[0061] (3) Dry the integrated lining brick blanks of the working layer magnesia carbon bricks and the permanent layer magnesia bricks at a drying temperature of 280±5°C for 14 hours to obtain an integrated high-performance lining brick for the converter. At this time, the strength of the magnesia carbon brick part is 35±10Mpa and the density is 2.98±0.02g / cm 3 The strength of the magnesia brick part is 100±20Mpa and the density is 3.03±0.02g / cm.
[0062] Table 3 Comparison of product indicators of Example 1 with national standards
[0063]
[0064]
[0065] Example 2
[0066] A method for preparing an integrated high-performance lining brick for a converter comprises the following steps:
[0067] (1) Weigh each raw material;
[0068] Table 4 Example 2 Working layer magnesia carbon brick raw material ratio table
[0069]
[0070] Table 5 Example 2 Permanent layer magnesia brick raw material ratio table
[0071]
[0072]
[0073] (2) Mixing and secondary molding operations:
[0074] (a) The permanent layer magnesia brick raw material is mixed with a wet mill to obtain a permanent layer magnesia brick mud material, the mixing speed is 100 rpm, the net mixing time is 28 min, and the discharge temperature is 52°C; the working layer magnesia carbon brick raw material is mixed with a high-speed mixer to obtain a working layer magnesia carbon brick mud material, the mixing speed is 360 rpm, the net mixing time is 15 min, and the discharge temperature is 56°C;
[0075] (b) The permanent layer magnesia brick mud is loaded into the permanent layer magnesia brick mold and pressed by an 800-ton electric screw brick press. The molding pressure is 8000KN. Press three times to obtain a strength of 30±5Mpa and a density of 2.80±0.04g / cm 3 The initial forming of magnesia brick green;
[0076] (c) The initially formed magnesia brick blank is placed in the corresponding position in the cavity of the integrated lining brick mold, and then the working layer magnesia carbon brick mud is loaded into the cavity of the integrated lining brick mold. A 1600-ton electric screw brick press is used for the second pressing and molding. The molding pressure is 16000KN, and it is pressed 10 times to obtain an integrated lining brick blank of the working layer magnesia carbon brick and the permanent layer magnesia brick. The overall strength of the brick blank is high, and the bonding strength between the magnesia brick and the magnesia carbon brick is high, and there is no problem of breakage between the two.
[0077] (3) Dry the integrated lining brick blanks of the working layer magnesia carbon bricks and the permanent layer magnesia bricks at a drying temperature of 280±5°C for 12 hours to obtain an integrated high-performance lining brick for the converter. At this time, the strength of the magnesia carbon brick part is 35±10Mpa and the density is 3.0±0.02g / cm 3 The strength of the magnesia brick part is 100±20Mpa and the density is 3.10±0.02g / cm.
[0078] Table 6 Comparison of product indicators of Example 2 with national standards
[0079]
[0080]
[0081] Example 3
[0082] A method for preparing an integrated high-performance lining brick for a converter comprises the following steps:
[0083] (1) Weigh each raw material;
[0084] Table 7 Example 3 working layer magnesia carbon brick raw material ratio table
[0085]
[0086] Table 8 Raw material ratio of permanent layer magnesia brick in Example 3
[0087]
[0088]
[0089] (2) Mixing and secondary molding operations:
[0090] (a) The permanent layer magnesia brick raw material is mixed with a wet mill to obtain a permanent layer magnesia brick mud material, the mixing speed is 100 rpm, the net mixing time is 33 min, and the discharge temperature is 54°C; the working layer magnesia carbon brick raw material is mixed with a high-speed mixer to obtain a working layer magnesia carbon brick mud material, the mixing speed is 360 rpm, the net mixing time is 18 min, and the discharge temperature is 56°C;
[0091] (b) The permanent layer magnesia brick mud is loaded into the permanent layer magnesia brick mold and pressed into shape by an 800-ton electric screw brick press with a molding pressure of 8000KN. The bricks are pressed three times to obtain a strength of 30±5Mpa and a density of 2.78±0.04g / cm 3 The initial forming of magnesia brick green;
[0092] (c) The initially formed magnesia brick blank is placed in the corresponding position in the cavity of the integrated lining brick mold, and then the working layer magnesia carbon brick mud is loaded into the cavity of the integrated lining brick mold. A 1600-ton electric screw brick press is used for the second pressing and molding. The molding pressure is 16000KN, and it is pressed 10 times to obtain an integrated lining brick blank of the working layer magnesia carbon brick and the permanent layer magnesia brick. The overall strength of the brick blank is high, and the bonding strength between the magnesia brick and the magnesia carbon brick is high, and there is no problem of breakage between the two.
[0093] (3) Dry the integrated lining brick blanks of the working layer magnesia carbon bricks and the permanent layer magnesia bricks at a drying temperature of 280±5°C for 14 hours to obtain the integrated high-performance lining bricks for the above-mentioned converter. At this time, the strength of the magnesia carbon brick part is 40±5Mpa and the density is 3.02±0.02g / cm 3 The strength of the magnesia brick part is 100±20Mpa and the density is 3.03±0.02g / cm.
[0094] Table 9 Comparison of product indicators of Example 3 with national standards
[0095]
[0096] In the embodiment, magnesium bricks and magnesium carbon bricks are introduced with magnesium aluminum alloy powder, which can generate liquid phase at high temperature to promote the sintering of bricks, wherein magnesia sand will react with the product of magnesium aluminum alloy powder oxidation or with microcrystalline corundum powder to generate magnesium aluminum spinel phase, which is helpful to fill pores, improve the density and strength of bricks, improve the resistance to slag erosion, and increase the load softening temperature. In addition, the introduction of magnesium aluminum spinel powder into the raw materials is conducive to the formation of magnesium aluminum spinel phase in the bricks, and is conducive to improving the thermal shock stability of the bricks.
[0097] From the physical and chemical indicators tested in the examples, the comprehensive performance of the products has been significantly improved, all significantly higher than the national standards. The compressive strength, volume density, and porosity of the magnesium bricks and magnesium carbon bricks in the examples have obvious advantages, and the anti-scouring and anti-erosion properties of the refractory materials have been significantly improved; the load softening temperature of the magnesium bricks in the examples is extremely high, and recycled materials are introduced into the raw materials of the magnesium bricks, which saves costs, recycles waste bricks, and realizes the sustainable development of energy; the high-temperature flexural strength of the magnesium carbon bricks in the examples is high, which can significantly improve the high-temperature performance and anti-scouring properties of the refractory materials.
[0098] The disclosed embodiments are described to enable one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing an integrated high-performance lining brick for a converter, characterized in that: The steps include: (1) Weigh each raw material; (2) Mixing and secondary molding operations: (a) mixing the raw material of permanent layer magnesia brick with a wet mill to obtain permanent layer magnesia brick mud; mixing the raw material of working layer magnesia carbon brick with a high-speed mixer to obtain working layer magnesia carbon brick mud; (b) placing the permanent layer magnesia brick mud into a permanent layer magnesia brick mold and pressing it into shape to obtain a preliminarily formed magnesia brick blank; (c) placing the initially formed magnesia brick blank into the corresponding position in the mold cavity of the integrated lining brick mold, and then loading the working layer magnesia carbon brick mud into the mold cavity of the integrated lining brick mold, and performing a second pressing molding to obtain an integrated lining brick blank of the working layer magnesia carbon brick and the permanent layer magnesia brick; (3) drying the integrated lining brick blanks of the working layer magnesia carbon bricks and the permanent layer magnesia bricks to obtain the integrated high-performance lining bricks for the converter; The integrated high-performance lining brick for the converter comprises a brick body, wherein the brick body comprises a permanent layer of magnesia bricks and a working layer of magnesia-carbon bricks, and the permanent layer of magnesia bricks and the working layer of magnesia-carbon bricks are connected via a slot structure; A plurality of card blocks are arranged on one side of the permanent layer magnesia bricks, and a plurality of card slots are arranged on one side of the working layer magnesia carbon bricks, and the card blocks are adapted to the card slots; The card block is a T-shaped card block or an L-shaped card block; The working layer magnesia carbon brick is made of the following raw materials in parts by weight: 10-30 parts of 3.5mm-6mm magnesia aggregate, 10-30 parts of 1-3.5mm magnesia aggregate, 10-30 parts of 0-1mm magnesia aggregate, 3-20 parts of F100-F200 magnesia powder, 10-18 parts of F100 flake graphite, 0.2-2 parts of solid resin powder, 0.5-3 parts of F325 chromium oxide green, 0.5-3 parts of 5μm-15μm microcrystalline corundum powder, 0.5-4.5 parts of F200 magnesium aluminum alloy powder, and 2.5-3.5 parts of liquid phenolic resin; The permanent layer magnesia brick is made of the following raw materials in parts by weight: 10-30 parts of 3.5mm-6mm magnesia sand aggregate, 10-30 parts of 1-3.5mm magnesia sand aggregate, 10-30 parts of 0-1mm magnesia sand aggregate, 0-20 parts of 3.5mm-6mm waste magnesium spinel bricks, 0-20 parts of 1-3.5mm waste magnesium spinel bricks, 0-20 parts of 0-1mm waste magnesium spinel bricks, 3-20 parts of F100-F200 magnesia sand powder, 0.05-0.2 parts of 2mm explosion-proof fiber, 0.2-2 parts of solid resin powder, 0.5-3 parts of 5μm-15μm microcrystalline corundum powder, 0.5-4.5 parts of F200 magnesium aluminum alloy powder, 2-10 parts of 5-15μm magnesium aluminum spinel powder, 2.5-3.5 parts of liquid phenolic resin, and 0.1-0.3 parts of methenamine.
2. The method for preparing an integrated high-performance lining brick for a converter according to claim 1, characterized in that: The longitudinal section of the brick body is a quasi-isosceles trapezoid, and the lower bottom of the quasi-isosceles trapezoid, i.e. the other side of the permanent layer of magnesium bricks, is designed with an arc, which is the same as the arc of the converter shell used.
3. The method for preparing the integrated high-performance lining brick for converter according to claim 1, characterized in that: In step (a), the permanent layer magnesia brick raw material is mixed with a wet mill, the mixing speed is 60-120 rpm, the net mixing time is 20-40 min, and the discharge temperature is 45-55° C.; The raw materials of the working layer magnesium carbon bricks are mixed with a high-speed mixer, the mixing speed is 120-360 rpm, the net mixing time is 10-30 min, and the discharge temperature is 50-60°C.
4. The method for preparing the integrated high-performance lining brick for converter according to claim 1, characterized in that: In step (b), the pressing molding is carried out at a molding pressure of 6300-1500 KN and the pressing is performed 2-3 times to obtain a strength of 20-40 MPa and a density of 2.5-2.8 g / cm 3 The initial formed magnesia brick green.
5. The method for preparing the integrated high-performance lining brick for converter according to claim 1, characterized in that: In step (c), the second pressing and molding is performed at a molding pressure of 10000-20000 KN and is performed 8-12 times to obtain an integrated lining brick blank of a working layer of magnesia carbon bricks and a permanent layer of magnesia bricks.
6. The method for preparing the integrated high-performance lining brick for converter according to claim 1, characterized in that: In step (3), the drying temperature is 200-300°C, the drying time is 12-20h, and the strength of the magnesia carbon brick part of the integrated high-performance lining brick for the converter is 25-40MPa and the density is 2.96-3.06g / cm 3 The strength of the magnesia brick part is 80-120MPa and the density is 3.00-3.13g / cm 3 .
Citation Information
Patent Citations
Converter spherical rounded-corner elbow furnace-lining structure
CN104962682A
Combined type steel ladle permanent layer casting body
CN104972103A
Composite converter magnesia-carbon brick and preparation method thereof
CN110423125A
Magnesia carbon brick for converter impact zone and preparation method of magnesia carbon brick
CN112250421A
Integrated high-performance lining brick for converter
CN219861426U
Cited By
Efficient energy-saving drying system for magnesia carbon brick production
CN224455297U